Implementation of in utero laparotomy-assisted fetoscopic spina bifida repair in two centers in Latin America: rationale for this approach in this regionAJOG Global Reports at a Glance - Jezid Miranda, PhD; Miguel A. Parra-Saavedra, PhD; William O. Contreras-Lopez, PhD; Cristóbal Abello, MD; Guido Parra, MD; Juan Hernandez, MD; Amanda Barrero, MD; Isabela Leones, MD; Adriana Nieto-Sanjuanero, MD; Gerardo Sepúlveda-Gonzalez, MD; Magdalena Sanz-Cortes, PhD (AJOG Global Reports)
Background: Spina bifida (SB) is a severe congenital malformation that affects approximately 150,000 infants annually, predominantly in low- and middle-income countries, leading to significant morbidity and lifelong disabilities. In Latin America, the birth prevalence of SB is notably high, often exacerbated by limited healthcare resources and poor access to advanced medical care. The implementation of laparotomy-assisted fetoscopic in-utero SB repair programs in Latin America targets reducing prematurity rates and enabling vaginal births while preserving the benefits of decreased need for hydrocephalus treatment and improved mobility in children. Objective: This study evaluated the safety, efficacy, and outcomes of laparotomy-assisted fetoscopic in-utero SB repair in Latin America compared to traditional open-hysterotomy methods. Study design: This retrospective cohort study included 39 cases of laparotomy-assisted fetoscopic in-utero SB repair, with 14 cases from Mexico (2017–2021) and 25 cases from Colombia (2019–2024). These cases were compared to 78 cases from the MOMs trial and 314 from other Latin American centers using traditional open-hysterotomy methods. Statistical analyses included the Student's t-test, Kruskal-Wallis test, and Pearson's chi-square test. Results: The gestational age (GA) at the time of surgery was significantly higher in fetoscopic centers (26±1.27 weeks) compared to the MOMs trial (23.6±1.42 weeks) and traditional hysterotomy methods (25.4±1 weeks) (P<.001). Mean GA at delivery was significantly earlier in the hysterotomy-based groups than in our fetoscopic group (MOMs: 34.1 [± 3.1] vs open-repair centers in LATAM: 34 [±3002] vs Fetoscopic: 35.3 [± 3.79] weeks; P values=.14 and 0004, respectively). Moreover, and the fetoscopic repair group exhibited a significantly lower rate of spontaneous preterm births (<34 weeks) at 15.8%, compared to 46.2% in the MOMs trial group and 49% in the other Latin American centers using traditional open-hysterotomy methods (P=.004 and .001, respectively). Additionally, the fetoscopic group had higher birthweights (2618±738g) and a lower cesarean delivery rate (65.8%) compared to the other groups (P<.001). Hydrocephalus treatment requirements at 12 months were similar across all groups. No maternal deaths or other outcomes such as pulmonary edema or need for maternal transfusion were noted in the fetoscopic SB repair group. Conclusion: The laparotomy-assisted fetoscopic SB repair offers a feasible and safer alternative to traditional hysterotomy-based techniques in Latin America. This approach significantly reduces the rates of prematurity and cesarean deliveries, facilitating vaginal births and minimizing maternal morbidity. These findings support the broader adoption of fetoscopic SB repair in regions with a high prevalence of SB and suboptimal perinatal outcomes, underscoring its advantages over hysterotomy-based approaches.